The study of new form of illustration to gain interest from the yongesters to know & appreciate national figure in memorial / Muhamad Ariful Shafiq Mohd Rais - Mohd Rais, Muhamad Ariful Shafiq (2015)
Illustration is the use of examples to make ideas more concrete and to make generalizations more specific and detailed. Examples enable writers not just to tell but to show what they mean. Illustration also is not straight forward. It is not easy to describe or classify, to typecast or to pin down, and less so now than ever before. Illustration is not an art and it also not graphic but illustration sit somewhere between art and graphic design. Another term often used to describe the discipline is commercial art, in recognition of the fact that much illustration is created for a client to fulfill a task or brief. This term describes illustration that is less about personal expression and more about satisfying a service, but to consider the discipline in this superficial manner is to barely scratch at the surface. Alongside speech, the drawn image has played a vital role in communication between people, and before the development of written language it was the only method of recording stories and tales. Illustrations come to existence to help us make sense to our world to allow us to record, describe, and communicate. Illustration create image for print, for screen, for galleries, and for architectural space. Illustration appears on book, magazines, posters, on websites, on clothing, and on TV.